Capacity building of nurses providing neonatal care in Rio de Janeiro, Brazil: methods for the POINTS of care project to enhance nursing education and reduce adverse neonatal outcomes - Darlow Brian A; Zin Andrea A; Beecroft Gina; Moreira Maria EL; Gilbert Clare E (BMC, 2012)
Abstract Background Increased survival of preterm infants in developing countries has often been accompanied by increased morbidity. A previous study found rates of severe retinopathy of prematurity varied widely between different neonatal units in Rio de Janeiro. Nurses have a key role in the care of high-risk infants but often do not have access to ongoing education programmes. We set out to design a quality improvement project that would provide nurses with the training and tools to decrease neonatal mortality and morbidity. The purpose of this report is to describe the methods and make the teaching package (POINTS of care--six modules addressing Pain control; optimal Oxygenation; Infection control; Nutrition interventions; Temperature control; Supportive care) available to others. Methods/Design Six neonatal units, caring for 40% of preterm infants in Rio de Janeiro were invited to participate. In Phase 1 of the study multidisciplinary workshops were held in each neonatal unit to identify the neonatal morbidities of interest and to plan for data collection. In Phase 2 the teaching package was developed and tested. Phase 3 consisted of 12 months data collection utilizing a simple tick-sheet for recording. In Phase 4 (the Intervention) all nurses were asked to complete all six modules of the POINTS of care package, which was supplemented by practical demonstrations. Phase 5 consisted of a further 12 months data collection. In Phase 1 it was agreed to include inborn infants with birthweight ≤ 1500 g or gestational age of ≤ 34 weeks. The primary outcome was death before discharge and secondary outcomes included retinopathy of prematurity and bronchopulmonary dysplasia. Assuming 400-450 infants in both pre- and post-intervention periods the study had 80% power at p = < 0.05 to detect an increase in survival from 68% to 80%; a reduction in need for supplementary oxygen at 36 weeks post menstrual age from 11% to 5.5% and a reduction in retinopathy of prematurity requiring treatment from 7% to 2.5%. Discussion The results of the POINTS of Care intervention will be presented in a separate publication. Trial registration Current Controlled Trials: ISRCTN83110114